Humanitarian aid and empowerment of Ukrainian refugees : the case of Visegrad Group countries: Czechia, Hungary, Poland and Slovakia - Moroń, Dorota; Madej, Małgorzata; Csoba, Judit (Routledge, 2025)
"The book presents good practices in humanitarian assistance and empowerment of Ukrainian refugees in various areas: emergency aid to large groups crossing the border, organisation of support in places of temporary stay, learning local languages, inclusion of children in school and adults in the labour market, and inclusion in the local community. It indicates the forms of international protection and the scope of their application by migrants from Ukraine, and discusses the temporary protection status dedicated to Ukrainian refugees. The volume will be of great interest to scholars and researchers of migration and diaspora studies, immigration law and public policy"--